2018
DOI: 10.1080/10641963.2018.1465076
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leech extracts on endothelial cell coagulation-related factors and endothelial dysfuction-related molecules

Abstract: In the present study, we found that PHL, a pepsin hydrolysate of leech with little anti-coagulatory effect, could significantly suppress TNF-α induced mRNA overexpression of endothelial dysfunction-related molecules (ET-1, iNOS, MCP-1, and IL-6). These results provide a reliable experimental basis for identifying new anti-atherosclerosis therapeutics for long term use and with minimal bleeding side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…In the MTT assay, it was shown that leech saliva at 48 h cause proliferation on the human endothelial cell line. 24 Different than our results, they observed proliferation of cells. This difference may be due to the use of distinct cell lines and types of leeches.…”
Section: Discussioncontrasting
confidence: 99%
“…In the MTT assay, it was shown that leech saliva at 48 h cause proliferation on the human endothelial cell line. 24 Different than our results, they observed proliferation of cells. This difference may be due to the use of distinct cell lines and types of leeches.…”
Section: Discussioncontrasting
confidence: 99%
“…The Leech ( Shuizhi , Hirudo) is the dried whole body of the Whitmania pigra Whitman, Hirudo nipponica Whitman or Whitmania acranulata Whitman ( ChPC, 2020 ). The Leech and its extracts can exert anti-atherosclerotic effects by regulating lipid metabolism, reducing oxidative stress, inhibiting inflammatory response and smooth muscle proliferation ( Gao et al, 2014 ; Wu et al, 2017 ; Xu et al, 2019 ). All of the above CHMs exhibit the typical multi-target and multi-component regulation effects on T2DM patients with CAS.…”
Section: Discussionmentioning
confidence: 99%
“…Leech and its extract have also been used in the treatment of cardiovascular diseases in TCM and can significantly weaken the atherosclerotic lesion area of ApoE −/− mice by means of a mechanism that potentially involves the inhibition of monocyte invasion of the vascular wall and improvement of vascular endothelial function. 41 , 42 In addition, various components in other Chinese herbal compounds, such as P. notoginseng saponins pns, 43 Poria cocos polysaccharide pcp, 44 and Alisol B23 acetate, 45 play an anti-AS role by reducing inflammation, inhibiting cholesterol synthesis, and regulating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%